FOREIGN LANGUAGE TEACHING OF FUTURE ENGINEERS: PROFESSIONALLY-ORIENTED APPROACH - Chevychelova, O.; Чевычелова, Е. А.; Чевичелова, О. О. (Харьковский национальный автомобильно-дорожный университет, 2016)
In the article the peculiarities of foreign language teaching at higher technical school are described, the importance of professionally-oriented approach to foreign language teaching is grounded and its essence is analyzed. The ways of implementing professionally-oriented ap-proach in higher technical education are considered.
ОБУЧЕНИЕ ИНОСТРАННОМУ ЯЗЫКУ БУДУЩИХ ИНЖЕНЕРОВ: ПРОФЕССИОНАЛЬНО-ОРИЕНТИРОВАННЫЙ ПОДХОД
НАВЧАННЯ ІНОЗЕМНОЇ МОВИ МАЙБУТНІХ ІНЖЕНЕРІВ: ПРОФЕСІЙНО-ОРІЄНТОВАНИЙ ПІДХІД
Keywords: foreign language; competence; professionally oriented approach; иностранный язык; компетенция; профессионально-ориентированный подход; іноземна мова; компетенція; професійно-орієнтований підхід; 378.147